Optimization and reflexivity in interdisciplinary agri-environmental scholarship - Chiles, Robert Magneson; Drohan, Patrick J.; Cibin, Raj; O'Sullivan, Lilian; Doody, Donnacha; Schulte, Rogier P. O.; Grady, Caitlin; Jiang, Fei; Preisendanz, Heather E.; Dingkuhn, Elsa L.; Veith, Tamie L.; Anderson, Aine (Frontiers in Sustainable Food Systems, 2023)
Introduction The Chesapeake Bay and Upper Bann watersheds in the United States and Northern Ireland, respectively, exemplify how agricultural systems contribute to groundwater and surface water pollution, which leads in turn to water quality issues in downstream water bodies. Interdisciplinary research, public outreach, and stakeholder engagement have received increased attention and consideration as pragmatic approaches for addressing these types of complex agri-environmental dilemmas. However, such approaches are far from guaranteed to improve water quality, as political-economic constraints, power asymmetries, cultural differences, divergent incentives, research gaps, and personality differences all complicate the process, and this can ultimately impact water quality efforts. Methods We present a holistic approach to addressing these challenges in the Chesapeake Bay and Upper Bann watershed management efforts by integrating the methodological strategies of optimization and reflexivity. Our use of these approaches, widely recognized as respective successful practices in quantitative and qualitative research, is novel in that it focuses directly on the researchers themselves as they discuss, evaluate, and develop potential solutions for complex agri-environmental water quality dilemmas. More specifically, our quantitative optimization is explored via a Functional Land Management (FLM) approach to land and natural resources management, while our qualitative reflexivity is explored through the process of participant observation. Results This paper provides a behind-the-scenes perspective on how interdisciplinary teams can improve their cooperation efficiency when addressing complex agri-environmental issues. In being reflexive, we sought to “optimize” on the methodological, ethical, social, and environmental possibilities of our scholarship. We found that our reflexive work on this project furthered our interest in FLM, a tool that embraced complexity and creativity over rigidity and oversimplification - the very same principles that guided our reflexive work. Discussion Throughout our collaborative investigation of FLM as a potential solution to soil and water quality issues, we came to appreciate that in order to better understand agri-environmental challenges issues, we also needed to better understand ourselves—our own disciplinary, cultural, and ethical standpoints. Reflexive approaches to research can provide practical guidance in this process by encouraging us to critique and analyze our assumptions, our methodologies, and the socio-historical context of our research.